Seasonal variations and source apportionment of carbonaceous aerosol in PM from a coal mining city in the North China Plain - Fanli Xue; Hongya Niu; Sihao Hu; Chunmiao Wu; Chongchong Zhang; Nana Gao; Xiulong Ren; Shujiao Li; Wei Hu; Jinxi Wang; Jingsen Fan (Energy Exploration & Exploitation, 2022)
Handan is one of the most polluted coal mining cities in the North China Plain (NCP). There is a lack of research on the pollution characteristics and sources of carbonaceous components in PM 2.5 in Handan city. Atmospheric PM 2.5 samples were collected from Handan City during 2018 and the organic carbon (OC) and elemental carbon (EC) in PM 2.5 were analyzed with a carbon analyzer. The annual average mass concentrations of PM 2.5 and total carbon (TC = OC + EC) in Handan were (101.88 ± 79.01) μg/m 3 and (28.03 ± 23.28) μg/m 3 , respectively. The annual average ratio of TC/PM 2.5 was (28.29% ± 7.95%), indicating that carbonaceous components made a major contribution to PM 2.5 . The seasonal variations of OC and EC concentrations in PM 2.5 were consistent with PM 2.5 , which was higher in winter and lower in summer. The annual average OC/EC ratio was (10.33 ± 5.83), and the (OC/EC) min ratio for each season was greater than 2, suggesting that there was probably secondary organic carbon (SOC) formation all around the year. The correlations between OC and EC during spring and winter were much more significant than during summer and autumn, which indicated that the sources of OC and EC in summer and autumn were more complex. Principal component analysis (PCA) displayed that the main sources of carbonaceous components in PM 2.5 were coal combustion emission, road dust and vehicle exhaust, which may be related to coal-fired power generation and steelmaking, and coal transportation in Handan city. The potential source contribution function (PSCF) analysis demonstrated that PM 2.5 and carbonaceous components in Handan city were significantly influenced by both local emissions and regional transport during the observation period.